THE UNIQUENESS OF USING NATIONAL VALUES IN THE EDUCATION OF CHILDREN OF PRESCHOOL AGE - Azamova daughter of Nargiza Nemat (Zeta Repository, 2023)
In Uzbek folk pedagogy, great attention has been paid to inculcating in children of preschool age such feelings as loving, compassionate, humane, loving the land that shed blood like a navel.